Effect of the Bolsa Familia Programme on the outcome of tuberculosis treatment: a prospective cohort study. Issue 2 (February 2019) - Oliosi, Janaina Gomes Nascimento; Reis-Santos, Barbara; Locatelli, Rodrigo Leite; Sales, Carolina Maia Martins; da Silva Filho, Walter Gomes; da Silva, Kerollen Cristina; Sanchez, Mauro Niskier; de Andrade, Kaio Vinicius Freitas; de Araújo, Gleide Santos; Shete, Priya B; Pereira, Susan Martins; Riley, Lee W; et al.
Summary: Background: Social protection interventions might improve tuberculosis outcomes and could help to control the epidemic in Brazil. The aim of this study was to evaluate the independent effect of the Bolsa Familia Programme (BFP) on tuberculosis treatment outcomes in Brazil. Methods: We prospectively recruited and followed up individuals (aged ≥18 years) who initiated tuberculosis treatment at 42 health-care centres across seven cities in Brazil, between March 1, 2014, and April 30, 2017. Patients were interviewed at health-care centres and information about individual characteristics, socioeconomic status, living conditions, lifestyle, and comorbidities was recorded. Patients were separated into two groups according to BFP beneficiary status: BFP (exposed) or non-BFP (not exposed). Treatment outcome (cure, dropout, death, or development of drug-resistant tuberculosis or treatment failure) was recorded after 6 months of therapy. Pearson's χ 2 test and ANOVA were used to compare tuberculosis treatment outcomes between the two groups, and we estimated the propensity score of being a beneficiary of the BFP using a logit model. We used multinomial regression models to evaluate the effect of the BFP on tuberculosis treatment outcomes. Findings: 1239 individuals were included in the study, of whom 196 (16%) were beneficiaries of the BFP and 1043 (84%) were not. After 6 months of treatment, 912 (87%) of 1043 patients in the non-BFP group and 173 (88%) of 196 patients in the BFP group were cured of tuberculosis, 103 (10%) patients in the non-BFP group and 17 (9%) patients in the BFP group had dropped out, and 25 (3%) patients in the non-BFP group and six (3%) patients in the BFP group had died. Three (<1%) of 1043 patients in the non-BFP group developed drug-resistant tuberculosis. Being a BFP beneficiary had a positive effect for cure (average effect 0·076 [95% CI 0·037 to 0·11]) and a negative effect for dropout (−0·070 [–0·105 to 0·036]) and death (−0·002 [–0·021 to 0·017]). Interpretation: BFP alone had a direct effect on tuberculosis treatment outcome and could greatly contribute to the goals of the WHO End TB Strategy. Funding: Brazilian National Council for Scientific and Technological Development (CNPq) and Brazilian Ministry of Health Department of Science and Technology (DECIT).